2023
DOI: 10.32604/cmc.2023.037154
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Resource Allocation in Unmanned Aerial Vehicles Based on Swarm Intelligence Algorithms

Abstract: Due to their adaptability, Unmanned Aerial Vehicles (UAVs) play an essential role in the Internet of Things (IoT). Using wireless power transfer (WPT) techniques, an UAV can be supplied with energy while in flight, thereby extending the lifetime of this energy-constrained device. This paper investigates the optimization of resource allocation in light of the fact that power transfer and data transmission cannot be performed simultaneously. In this paper, we propose an optimization strategy for the resource all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
0
0
Order By: Relevance
“…However, the algorithm complexity is high, and the default number of users meets antenna constraints, which does not meet the access situation of users in practical applications. Reference [20] used swarm intelligence optimization algorithms to study resource allocation problems in communication systems, and the results showed that swarm intelligence optimization algorithms performed well in the field of resource allocation. Literature [21] proposed a bald eagle search algorithm (BES), which can effectively solve various complex numerical optimization problems.…”
Section: Introductionmentioning
confidence: 99%
“…However, the algorithm complexity is high, and the default number of users meets antenna constraints, which does not meet the access situation of users in practical applications. Reference [20] used swarm intelligence optimization algorithms to study resource allocation problems in communication systems, and the results showed that swarm intelligence optimization algorithms performed well in the field of resource allocation. Literature [21] proposed a bald eagle search algorithm (BES), which can effectively solve various complex numerical optimization problems.…”
Section: Introductionmentioning
confidence: 99%